Juridical Analysis of the Application of Legal Protection to the Rights of Indonesian Migrant Workers (Research Study at the Batam Migrant Worker Protection Service Post (P4MI) - Darwin Simanjuntak; Darwis Anatami; Parameshwara; Erniyanti; Soerya Respationo (MultiTech Publisher, 2023)
The purpose of the protection of Indonesian Migrant Workers as stated in Article 3 of Law Number 18 of 2017 concern the Protection of Indonesian Migrant Workers is to ensure the fulfillment and enforcement of Human Rights as Indonesian citizens and migrant workers as well as to ensure legal, economic, and social protection. Indonesian migrant workers and their families. This research uses the library research method or library research. The data sources used are primary and secondary data from press releases, as well as data from the Batam City Placement and Protection Service Post for Indonesian Migrant Workers (P4MI), then the data were analyzed by descriptive analysis method. Every prospective Indonesia Migrant worker has the same rights and obligations to get a job abroad and choose a job according to his competence, gain access to self-capacity through education and job training, and obtain correct information about the job market, placement procedures, and conditions. Based on the data analysis conducted, it is concluded that the government’s efforts to provide legal protection for Indonesian Migrant Workers so far can be seen from the form of legislation issued in response to the needs of Indonesian Migrant workers.